Water scarcity and welfare: Regulated public–private supply chain versus spot-market competition. (3rd August 2022) - Kogan, Konstantin; Tsadikovich, Dmitry; Avinadav, Tal
Abstract: Despite legislation and price controls by the government and state agencies that typically assume responsibility for providing water services, water bills continue to rise. However, this has not prevented growth in overall water consumption, nor an increase in water scarcity, both of which are fueled by worldwide population growth, urbanization, and demand for a higher quality of life. Market-based competition is thought to be a promising approach to controlling water charges and managing water scarcity. We compare a spot-market-based competitive supply model for water, which determines the equilibrium price, with a supply chain approach, in which a non-profit public entity encourages competition between private water providers within the framework of a regulated, time-invariant price. We derive dynamic equilibrium replenishment and inventory policies and show that, contrary to expectations, spot-market competition does not necessarily result in greater levels of supply, nor in a lower price, than does a regulated supply chain. Furthermore, the public-private partnership can have an additional advantage in the form of both higher consumption and higher consumer welfare. However, increasing the distribution cost, and hence, the regulated price is likely to diminish the differences between the two market types.